A group action on pandiagonal lanna magic squares - Unyamanee Seanprom (2018)
© 2018 by the Mathematical Association of Thailand. All rights reserved. In this paper we use a concept of group action on subgroup of S16to find the number of all pandiagonal Lanna magic squares generated from a set of Myanmar numbers found in a 4x4 non-normal Lanna magic square, called Buddha Khunnung 56 Yantra. Those numbers are 1-15 with repeated 8. This magic square is a talisman from Lanna Kingdom, an ancient kingdom of Thailand. The study found that there were 384 pandiagonal Lanna magic squares.